PENERAPAN PERMAINAN SIRKUIT DALAM MENSTIMULASI PERKEMBANGAN MOTORIK PADA ANAK DI SENTRA WIRAJAYA MAKASSAR - Firdaus, Faradillah; Afif, Nur; Naz, Jameel Ramzi; Adrianty, Nurul Adha (LPPM Institut Pendidikan Nusantara Global, 2022)
Rough motoric development is an important aspect of every individual. Rough motoric development is very important and it is hoped that it will become a development that has been fulfilled in children because it can affect the physical and intellectual condition of a child. This activity aims to stimulate motoric development in children at Sentra Wirajaya Makassar who are still quite difficult to read and recognize letters by implementing circuit games. The implementation method used is pre-experimental with a one shot case study design. There were 10 children participating in this activity. Data collection techniques in this activity use observation and children's rough motoric instruments. The results obtained are the application of circuit games can be an alternative to stimulate rough motor development in children. This is indicated by all children showing the developmental stage, from good to very good. Participants also showed a positive response in the form of enthusiasm shown.